Pengaruh Emotional Intelligence dan Reward Terhadap Kinerja Karyawan dalam Etika Bisnis Islam: Studi pada Karyawan Generasi Z PT Asuransi Astra Buana Cabang Bandar Lampung - Cahya Komala Dewi; Okta Supriyaningsih; Muhammad Iqbal Fasa (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the influence of emotional intelligence and reward onemployee performance among Generation Z within the framework of Islamic business ethics. The research was conducted at PT Asuransi Astra Buana, Bandar Lampung Branch, using a quantitative approach. Data were collected through questionnaires distributed to 35 respondents and analyzed using the Partial Least Squares (PLS) method. The analysis results indicate that neither emotional intelligence nor reward has a significant effect, whether partially or simultaneously, on employee performance. This is reflected in the significance values of the T and F tests, which exceed 0.05, and the very low R-Square value (0.015). These findings suggest that in the context of Generation Z employees at the company, other factors may have a more substantial influence on performance. The study highlights the importance of a more holistic managerial approach that aligns with the values of justice and balance as emphasized in Islamic business ethics.